ISLAM DAN TANTANGAN KEMISKINAN DI INDONESIA: TELAAH PEMIKIRAN ALI ASGHAR ENGINEER - Thohari, Ahmad Miftahudin (Academic Journal of Islamic Principles and Philosophy, 2022)
Poverty is still a problem that needs to be solved in Indonesia. As a country with abundant natural resources, Indonesia should be able to become one of the most developed countries in the world. However, poverty is still a problem that is difficult to solve. The system of global capitalism in the industrialized world is a scourge in itself for the perpetuation of economic inequality for the lower classes and the confinement of poverty. On the other hand, as a country where the majority of the population is Muslim, Islamic values that uphold human dignity have not been seen as a value system that can be implemented as a policy to help the Indonesian government alleviate the problem of poverty. Through descriptive library research, this article provides a description of how Islam must be interpreted in order to provide answers to the problem of poverty that occurs in Indonesia by examining Ali Asghar Engineer’s critical thinking related to Islam and the challenge of poverty.